2021
DOI: 10.1091/mbc.e20-06-0382
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping roles of JIP3 and JIP4 in promoting axonal transport of lysosomes in human iPSC-derived neurons

Abstract: The dependence of neurons on microtubule-based motors for the movement of lysosomes over long distances raises questions about adaptations that allow neurons to meet these demands. Recently, JIP3/MAPK8IP3, a neuronally enriched putative adaptor between lysosomes and motors, was identified as a critical regulator of axonal lysosome abundance. In this study, we establish a human induced pluripotent stem cell (iPSC)-derived neuron model for the investigation of axonal lysosome transport and maturation and show th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(92 citation statements)
references
References 55 publications
10
82
0
Order By: Relevance
“…In Control i 3 Neurons, consistent with previous reports (Gowrishankar et al, 2021), most LAMP1 vesicles are largely concentrated in the soma with relatively fewer vesicles observed in neurites (Fig. 5 A, B).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…In Control i 3 Neurons, consistent with previous reports (Gowrishankar et al, 2021), most LAMP1 vesicles are largely concentrated in the soma with relatively fewer vesicles observed in neurites (Fig. 5 A, B).…”
Section: Resultssupporting
confidence: 91%
“…We next examined the distribution of different lysosomal proteins in these i 3 Neurons at 14 days differentiation. Staining with LAMP1, a marker of late endosomes as well as degradative lysosomes (Lie et al, 2021;Gowrishankar et al, 2021;Cheng et al, 2018;Yap et al, 2018), revealed that there was a significant increase in size of LAMP1-positive vesicles in the cell bodies of AP-4 i 3 Neurons (Fig. 1 C, D; Fig.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations